Hubungan Status Gizi dengan Angka Kejadian ISPA Akut pada Balita Usia 0-11 Bulan Disumatra Utara pada Tahun 2018 - Maria Lasfrida Silalahi; Tahoma Mutiara Siahaan; Sanggriani Mairanda; Maximilianus Wira (Yayasan Literasi Sains Indonesia, 2023)
Developmental problems in children in Indonesia and in developing countries are generally caused by two things, namely poor nutritional conditions and infectious diseases. The high number of Upper Respiratory Tract Infection (URTI) is caused by one of the factors that must also be known by the public is the nutritional status including malnutrition. This study aims to find the correlation between of nutritional status with the incidence of ispa in toddlers in the tompaso health center of minahasa regency. This research used quantitative with a cross sectional approach. Sampling in this study using the Purposive Sampling method obtained the number of samples as many as 100 respondents. The study was conducted by calcilating of z-score nutritional status of toddlers according to WHO and according to health professional assesment. The data analyzed using the Chi-square test. of the study based on nutritional status characteristics obtained malnutrition as many as 8 toddlers, malnutrition as many as 10 toddlers, then the characteristics of ARI were obtained who temporarily experienced ARI as many as 12 toddlers and those who did not or had previously experienced ARI as many as 6 toddlers. Based on the characteristics of the nutritional status of children under five in the working area of the Delitua Health Center, Deli Serdang Regency, they are in the good nutrition category, the incidence of ISPA in children under five at the Tompaso Health Center, Kab. Minahasa is in the category of temporarily experiencing ARI. There is a relationship between nutritional status and the incidence of ARI in toddlers at the Delitua Health Center, Deli Serdang Regency